(untitled) (Journal of Mechanical Engineering, 2019)
Fused deposition modelling (FDM) is one of the low cost additive manufacturing (AM) process. The feed stock filament of FDM is the only consumable in the process and by preparing (in-house) bio compatible feed stock filament the application domain can be increased. Some studies have reported the use of twin screw extrusion (TSE) process for preparation of bio compatible feed stock filament (comprising of polyvinyl chloride (PVC) and polypropylene (PP) and hydroxyapatite (HAp) particles) with improved mechanical, dimensional and thermal properties, for commercial FDM setup. But hitherto very less has been reported on process capability of in-house prepared biocompatible feed stock filament. In the present work statistical analysis (for tensile strength, hardness and dimensional accuracy) has been performed for investigations of process capability. The results have been also supported by control charts (X-chart and R-chart) based upon the best feedstock filament wire.